Antioxidant systems and lipid peroxidation in from Mid-Atlantic Ridge hydrothermal vent fields - Bebianno, Maria João (2020)
Enzymatic defenses involved in protection from oxygen radical damage were determined in gills and mantle of Bathymodiolus azoricus collected from three contrasting Mid-Atlantic Ridge (MAR) hydrothermal vent fields (Menez-Gwen, Lucky Strike and Rainbow). The activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidases (GPx) (total and Se-dependent), and levels of total oxyradical scavenging capacity (TOSC), metallothioneins (MT) and lipid peroxidation (LPO) were determined in B. azoricus tissues and the impact of metal concentrations on these antioxidant systems and lipid peroxidation assessed. SOD, CAT, TOSC, MTs and LPO levels were higher in B. azoricus gills while glutathione peroxidases (total and Se-dependent) were higher in the mantle, and with the exception of CAT, were of the same order of magnitude as in other molluscs. TOSC levels from Menez-Gwen indicate that the vent environment at this site is less stressful and the formation of ROS in mussels is effectively counteracted by the antioxidant defense system. TOSC depletion indicates an elevated ROS production in molluscs at the other two vent sites. Cytosolic SOD, GPx and LPO were more relevant at Lucky Strike (Bairro Alto) where levels of essential (Cu and Zn) and toxic metals (Cd and Ag) were highest in the organisms. CAT activity and LPO were predominant at the Rainbow vent site, where an excess of Fe in mussel tissues and in vent fluids (the highest of all three vent sites) may have contributed to increased LPO. Therefore, three distinct pathways for antioxidant enzyme systems and LPO based on environmental metal speciation of MAR vent fields are proposed for Bathymodiolus gills. At Menez-Gwen, TOSC towards peroxyl and hydroxyl radicals and peroxynitrite are predominant, while at Lucky Strike cytosolic SOD activity and GPx are the main antioxidant mechanisms. Finally at Rainbow, catalase and lipid peroxidation are dominant, suggesting that resistance of mussels to metal toxicity at these vent fields decreases in the sequence Menez-Gwen > Lucky Strike and Rainbow.